2019
DOI: 10.24874/ti.2019.41.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Wear behavior of Hybrid Aluminum Metal Matrix Composites

Abstract: The focus of the paper is the wear behavior of hybrid aluminum metal matrix composites. The main objective of the investigation is to conduct the wear test at room temperature for both the as-cast and age hardening conditions. Materials chosen for the study are Aluminum 7075 as a matrix, Silicon Carbide and Alumina are the reinforcements. Hybrid metal matrix composites are produced by utilizing stir casting route for 5-15 wt.% silicon carbide and alumina. Microstructural characterization of hybrid aluminum met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
5
17
0
Order By: Relevance
“…wear rate. It was observed that the volumetric wear rate decreased in heat treated hybrid aluminum metal matrix composites with increased SiC + Al 2 O 3 reinforcement and aging when compared with the base alloy the weight loss was decreased [23,24] in metal matrix composites. In hybrid aluminum metal matrix composites the weight loss was further reduced when compared with aged conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…wear rate. It was observed that the volumetric wear rate decreased in heat treated hybrid aluminum metal matrix composites with increased SiC + Al 2 O 3 reinforcement and aging when compared with the base alloy the weight loss was decreased [23,24] in metal matrix composites. In hybrid aluminum metal matrix composites the weight loss was further reduced when compared with aged conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Rajesh et al [4][5][6][7] conducted experimentations like hardness, wear behavior at as-cast and age hardened conditions etc. on aluminum hybrid metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…In an investigation, Rajesh et al [8,9] have analyzed the effect of reinforcing Al 2 O 3 and SiC on the wear behaviour of hybrid aluminium MMCs on a pin-on-disc tribometer. ey fabricated the composites by using the reinforcement SiC with 5%, 10%, and 15% weight and Al 2 O 3 with 5%, 10%, and 15% weight through stir casting.…”
Section: Introductionmentioning
confidence: 99%
“…Different investigators have taken different weight fractions of the reinforcement. Rajesh et al [9] have taken 5%, 10%, and 15% of the reinforcement. Fenghong et al [5] considered wt.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that impact strength and hardness increased with an increment in weight percentage of SiC. Rajesh and Kaleemulla [5][6][7] conducted experimentations such as hardness and wear behavior at as-cast and age hardened conditions on HAMMCs. The matrix material considered is Al7075, and the reinforcement material is SiC and Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%